2022
DOI: 10.1039/d2em00328g
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of the deposition of submicron soot particles on leaves of Platanus acerifolia tree

Abstract: Submicron soot particles (<1.0 μm in aerodynamic diameter) are responsible for global warming and health burdens worldwide. However, studies on bio-monitoring of submicron soot particles and their associated sources by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…The leaf samples were collected in the urban area of Nanjing from June to July (Summer) 2023, respectively. The collection of leaf samples was conducted based on previous studies and under the National Atmospheric Deposition Programme (NADP) monitoring initiative protocol [19,20]. Briefly, the leaf samples were taken from 30 species of plants, which are Eucommia ulmoides, Koelreuteria paniculata, Osmanthus fragrans, Buddleja Davidii, Platanus acerifolia, Fatsia japonica, Hedera Helix, Eriobotrya japonica, Cerasus yedoensis, Sapindus mukorossi Gaertn., Hydrangea macrophylla (Thunb.)…”
Section: Sample Collectionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The leaf samples were collected in the urban area of Nanjing from June to July (Summer) 2023, respectively. The collection of leaf samples was conducted based on previous studies and under the National Atmospheric Deposition Programme (NADP) monitoring initiative protocol [19,20]. Briefly, the leaf samples were taken from 30 species of plants, which are Eucommia ulmoides, Koelreuteria paniculata, Osmanthus fragrans, Buddleja Davidii, Platanus acerifolia, Fatsia japonica, Hedera Helix, Eriobotrya japonica, Cerasus yedoensis, Sapindus mukorossi Gaertn., Hydrangea macrophylla (Thunb.)…”
Section: Sample Collectionsmentioning
confidence: 99%
“…Cai et al [18] documented that the average deposition of PM on leaves was estimated to be 1.71 ± 0.05 g m −2 wk −1 after summarizing 150 studies conducted in 15 countries from 1960 to 2016. Terrestrial trees can considered an effective low-cost, low-energy strategy for removing BC from the atmosphere [19,20]. Some large-scale experiments, including the European Cooperative Air Quality Assessment Network using Bio-indicator Plants and the European Atmospheric Heavy Metal Deposition Survey, have been conducted in European countries to measure the metal and particulate matter deposited on leaves in the air [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A review conducted by Cai et al [4] estimated that the mean deposition of PM on leaves was 1.71 ± 0.05 g m −2 •wk −1 after reviewing 150 studies derived from 15 countries. Black carbon aerosols are a major component of ambient PM, and they are released from the incomplete combustion of liquid and solid fuels [5][6][7][8]. Studies have demonstrated that using plants is an environmentally friendly strategy with a low cost to remove black carbon particles in anambient environment [4,7].…”
Section: Introductionmentioning
confidence: 99%